Efficacy of Low-Intensity Pulsed Ultrasound for Orthodontic Pain Control: A Randomized Clinical Trial - Mohammadreza Badiee; Azita Tehranchi; Parsa Behnia; Karen Khatibzadeh (Tehran University of Medical Sciences, 2021)
Objectives: This study aimed to assess the efficacy of low-intensity pulsed ultrasound (LIPUS) for orthodontic pain control. Materials and Methods: This spilt-mouth randomized controlled clinical trial was performed on 44 mandibular first molars of 22 orthodontic patients at the Orthodontics Department of Shahid Beheshti Dental University. Elastomeric separators were placed at the mesial and distal of mandibular right and left first molars by separating pliers. Randomly, LIPUS was used at one side for 7 min and the same device with 0-degree intensity was used as sham for the other side on the facial skin. The same procedure was repeated after 24 h. Patients recorded their level of pain at 1, 6, and 24 h, and also on days 2 to 7 after, using a visual analog scale (VAS). Results: The effect of type of treatment (P=0.019), time of assessment (P<0.000) and the interaction effect of type of treatment and time of assessment (P=0.055) on the pain score were all significant. The mean pain score in the LIPUS group was significantly lower than that in the control group at 24 h (P=0.002), 4 days (P=0.031) and 5 days (P=0.035). Conclusion: LIPUS can be safely used during orthodontic treatment for pain control since it is safe, non-invasive, low-cost, and easy to use.